Assessment of lip profile and metric correlations through stereophotogrammetry in patients with unilateral cleft lip and palate - Neves, Maria Carolina (2024)
Cleft lip and palate are among the most common birth defects of the face. The anatomical changes caused by this condition aesthetically and functionally impact the individual\'s life. Therefore, the objective of the present study was to evaluate and measure the characteristics of the lips and the lower third of the face in patients with unilateral cleft lip and palate and patients without clefts, using the stereophotogrammetry technique. Two groups were obtained - (G1, 24 females, 6 males; aged between 20 and 60 years, mean age 44.0±12.0 years) and 30 patients without cleft (G2, 23 females, 7 males; aged between 20 and 59 years, mean age 43.5±12.0 years). Anthropometric points were determined on the surface of the face and the images were captured. Statistical analysis was performed to compare the groups, with a significance level set at 0.05. The comparative analysis revealed statistically significant differences in 5 linear measurements and 6 angular measurements. Linear measurements such as philtrum width, upper and lower lip skin height, mandibular ramus length and midfacial depth exhibited significant differences between cleft and non-cleft patients. Likewise, angular measurements, including upper lip angle, Cupid\'s bow angle, lower/middle facial convexity, lip seal, nasolabial angle, and left gonial angle showed statistically significant differences. In this way, the challenges present in the rehabilitation of patients with clefts are noted, reinforcing the need for analysis and treatment planning on an ongoing basis.